Distribution of Available S in Some Soil Series of West Bengal Growing Rice and Pulses - Hembram, Sandip; Mukhopadhyay, Prabir; Patra, P. K. (International Journal of Bio-resource and Stress Management, 2023)
Laboratory experiment was conducted to study the distribution of available S and to find out influence of different soil characteristics on the predictability of available S status in sixteen different soil series of West Bengal growing rice and pulses. Available (CaCl2 extractable) S content of soils under study showed wide variation ranging from 16.66 to 51.57 with an average of 35.60 mg kg-1 soil and considering the availability index (viz., available S<10 ppm (low); between 10-20 ppm (medium) and >20 ppm (high), 13% of the soils could be classified under medium and 87% under high available S status. The variation of available S status in soils of different series was due to variation in different soil properties, soil and crop management practice and fertilizer use, etc. Correlation coefficient values among different soil properties revealed significant influence of clay, total P, total S and amorphous Al content of the soils with their respective relative contributions of 58, 13, 6, 5 and 2% in the variation in available S status in soils.